Deciphering the deterministic role of TCR signaling in T cell fate determination - Qin, Zhen; Xu, Tao (Frontiers in Immunology, 2025)
T cell receptor (TCR) signaling, also known as signal 1, plays a crucial role in the activation and proliferation of T cells. The question of whether TCR signaling exerts a deterministic role in T cell fate determination is an area of active investigation. It has been particularly challenging to address this question due to the complexities associated with genetic manipulation of TCR signaling components, which often disrupts thymic T cell development or impairs T cell activation upon TCR engagement. Recent study demonstrates that the TCR-Lck/Fyn axis directly induces STAT3 phosphorylation and synergizes with pro-inflammatory cytokines to optimize STAT3 phosphorylation during Th17 cell differentiation. Additionally, the TCR-Lck/Fyn-AKT/mTOR axis negatively regulates Treg cell differentiation. In CD8+ T cells, persistent high-affinity antigen stimulation drives differentiation along the exhaustion pathway, while acute infection or intermediate antigen levels promote differentiation into effector and memory T cells, although the underlying mechanism remains to be fully elucidated. Collectively, these studies provide compelling evidence that TCR signaling has a deterministic impact on T cell fate. This review summarizes recent advances in understanding how TCR signaling shapes T cell fate determination.